Pengaruh Konsumsi Kurma (Phoenix Dactylifera) terhadap Kenaikan Kadar Hemoglobin : A Review - Alfiah Rahmawati; Yuna Silviana (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2019)
A condition where red blood cells ammount is not enough for physiological need is called Anemia, one of general cause of anemia is because less of iron. Anemia can give bad impact for the pregnant mother because low of haemoglobin levels that is (11 g/dl). One of ways to prevent anemia on pregnant mother is given dates. Dates has benefit such as increase platelets level, prevent blood clots, stoke and heart attack, uterine bleeding, watery brain on fasting, increase stamina, inhibits the aging process, preven constipation, launch defecate, lowers cholesterol in the blood, keep eye health and good for nerve health. Searching article is done with database such as google scholar. The keyword is “anemia”, “pregnant mommy/ibu hamil”, “dates/kurma” and the writer found 7 articles that relevant from 2013-2019. Dates contains real sugar in glucose and fructose form, rich of protein, fiber, mineral such as iron, calsium, sodium, and potasium.